2022
DOI: 10.3390/math10020178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Source Position in Fluid Flow, Heat Transfer and Entropy Generation in a Naturally Ventilated Room

Abstract: In this study, a 3D numerical study of free ventilated room equipped with a discrete heat source was performed using the Finite Volume Method (FVM). To ensure good ventilation, two parallel openings were created in the room. A suction opening was located at the bottom of the left wall and another opening was located at the top of the opposite wall; the heat source was placed at various positions in order to compare the heating efficiency. The effects of Rayleigh number (103 ≤ Ra ≤ 106) for six heater positions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The aforementioned sources provide thermal energy, which may be applied to various tasks, including cooking, heating, and producing electricity. A study by M. A. Alghaseb et al [11] used 3D numerical analysis to look into a room with good air flow and a single heat source. They found that where the heating device is placed has a big effect on how the flow behaves and how high it goes in the room when it is placed on a vertical surface close to the extraction opening.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned sources provide thermal energy, which may be applied to various tasks, including cooking, heating, and producing electricity. A study by M. A. Alghaseb et al [11] used 3D numerical analysis to look into a room with good air flow and a single heat source. They found that where the heating device is placed has a big effect on how the flow behaves and how high it goes in the room when it is placed on a vertical surface close to the extraction opening.…”
Section: Introductionmentioning
confidence: 99%
“…Tominaga [24] conducted numerical simulations (CFD) to study the airflow around isolated gable-roofed buildings with different roof slopes and found significant differences in the flow fields for slope ratios of 3:10 and 5:10. Additionally, there are also studies related to wind towers, wind catchers, Mansard roofs, and other structures on rooftops [25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%